PORTRAYING CONCEPT OF INDONESIA THROUGH TEXTUAL ANALYSIS AND DISCOURSE PRACTICE IN INDONESIAN MINISTRY OF TOURISM’S SLOGANS - RIZQIYA, LAYLA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Critical Discourse Analysis, Discourse Practice, Slogan, IndonesianMinistry of Tourism.The use of language as communication media to persuade people in advertising is realized by the Indonesian Ministry of Tourism in form of slogans. The writer conducted a study about portraying concept of Indonesia through textual analysisand discourse practice in Indonesian ministry of tourism’s slogans to elaborate more understanding toward the slogans. There are two problems to be solved in this study, namely: (1) What are the language aspects which construct the meaning of “Indonesia Ultimate in Diversity”, “Visit Indonesia 2008. Celebrating 100 Years of National Awakening”, and “Wonderful Indonesia” (2) How is discursive practice applied in “Indonesia Ultimate in Diversity”, “Visit Indonesia 2008.Celebrating 100 Years of National Awakening”, and “Wonderful Indonesia” The method of this study was qualitative approach. The writer focused on analyzing the slogans using two elements of critical discourse analysis proposed by Fairclough which are textual analysis and discourse practice.This study revealed that each slogan produced by The Ministry of Tourisms draws concept of Indonesia such as underlining the concept of diversity on Indonesia, emphasizing the historical events in Indonesia, and the latest slogan provides wider concept of Indonesia that enable everyone to interpret in various way.This study is expected to give more understanding about the concept of Indonesia that the Ministry of Tourism brought in form of slogans. The writer suggested next researchers investigate wider and deeper study about slogans using all three dimensions of CDA by Fairclough or using theory proposed by different expert like Teun Van Dijk.